2015
DOI: 10.1080/10910344.2014.991029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High-Pressure Coolant Assistance on the Machinability of the Titanium AlloyTi555–3

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. ABSTRACTThe originality of this paper is the quantification of productivity gains and the improvement in surface integrity seen for a recent titanium alloy that is seeing increasing use in the aeronautical industry. The Ti555-3 titanium alloy, which is starting to find greater application in the aeronautical field, exhibits certain difficulties in terms of mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The graphical representation demonstrates that the average surface roughness gradually reduces as the cutting velocity increases. This can be related to the work material's local thermal softening (a less thermally conductive Ti-6Al-4V alloy confines heat for an extended period) at a specific temperature, as shown in another research finding [34]. Additionally, less BUE generation with a smaller contact area and less chattering at a faster cutting velocity [11] decrease surface roughness.…”
Section: Effect On Surface Roughness (R a )mentioning
confidence: 90%
“…The graphical representation demonstrates that the average surface roughness gradually reduces as the cutting velocity increases. This can be related to the work material's local thermal softening (a less thermally conductive Ti-6Al-4V alloy confines heat for an extended period) at a specific temperature, as shown in another research finding [34]. Additionally, less BUE generation with a smaller contact area and less chattering at a faster cutting velocity [11] decrease surface roughness.…”
Section: Effect On Surface Roughness (R a )mentioning
confidence: 90%
“…6 B illustrates the average tool-chip friction coefficient µ determined by Eq. (4) when machining Inconel 718 with Ti 0.55 Al 0.45 N coated carbide tools with various coating thicknesses [18] . Compared to the Ti 0.55 Al 0.45 N coated carbide tools with coating thicknesses of 1.6 µm and 2.5 µm, a low average friction coefficient could be obtained by Ti 0.55 Al 0.45 N coated carbide tools with coating thicknesses of 2 µm and 3 µm.…”
Section: Physical Properties Of Tialn Coatingmentioning
confidence: 99%
“…Also in the case of titanium alloys, research in the field of LAM machining can be found [40]. Braham-Bouchnak et al [8] studied the effect of laser assistance on the machinability of the Ti533-3 alloy. They showed a reduction in cutting forces with increasing temperature, which is significantly influenced by cutting parameters and laser power.…”
Section: Introductionmentioning
confidence: 99%